Peran Guru Dalam Pengelolaan Kelas Terhadap Prestasi Siswa Selama Proses Pembelajaran Materi PKN - Pingki Lestari; Siti Istiqomah; Khasbi Ainun Najib (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Optimal classroom management is one of the important factors in supporting the success of the teaching and learning process, especially at the primary school level. Teachers have an important role as organizers of classroom dynamics, by creating a comfortable learning atmosphere, encouraging educational interactions, and fostering students' enthusiasm for learning. This article aims to examine the effect of the teacher's role in managing the classroom on improving student learning achievement in Civics Education (PKN) subjects in grade 4 SD. Using a qualitative approach based on a literature study, this article reviews the teacher's role in arranging the classroom, choosing appropriate learning strategies, and managing student behavior effectively. The findings of the discussion show that students' active involvement in learning, understanding of Civics Education materials, and their learning outcomes are greatly influenced by the quality of classroom management by teachers. Therefore, teachers are required to have good pedagogical and managerial skills to create meaningful and effective learning.